FAKTOR FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN AKUNTANSI SUMBER DAYA MANUSIA PADA PERBANKAN - Rani Eka Diansari; Sheftyka Rispin (Akademi Akuntansi YKPN Yogyakarta, 2019)
This study aims to determine the effect of firm size on human resource accounting disclosure, the effect of profitability on human resource accounting disclosure and the effect of company age on human resources accounting disclosure. The population of this study are banking companies listed on the Indonesia Stock Exchange in 2015-2017 with a sample of 120 samples. The sampling technique uses purposive sampling method. The data used is secondery data. Analytical technique used are descriptive statistical analysis, classical assumption test, multiple linear regression, F test, t test and R2 test. The result of the study concluded that 1.) the value of the company sixe was 2,870 and a significance value of 0,005. This proves that the size of company has a significant positive effect on human resource accounting disclosure, 2.) the profitability value is -0,585 and the significance value is 0,560. This proves that profitability has a negative effect not significant on human resource accounting disclosure and 3.) the value of the company age is 1,616 and the significance value is 0,109. This proves that the age company has no significant positive effect on human resource accounting disclosure. Keywords: company size, profitability, company age, human resource accounting disclosure